Effectiveness of Kindness Behavior Training on Interpersonal Communication Skills and Self-Regulation in Depressed Individuals with Substance Use Disorder - Shah Hosseini, Mahtab; Mohammadi, Akbar (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the effectiveness of kindness behavior training on enhancing interpersonal communication skills and self-regulation, and reducing depressive symptoms in depressed individuals with substance use disorder.Methods and Materials: The research employed a quasi-experimental design with pre-test and post-test assessments, including a control group. The statistical population consisted of individuals with substance use disorder referred to the Welfare Organization Addiction Treatment Center in Semnan, Iran. A total of 30 participants were selected through random sampling and were assigned to experimental (n = 15) and control (n = 15) groups. The experimental group received eight 90-minute sessions of Kindness Behavior Training (KBT), while the control group received no intervention. Data collection tools included the Beck Depression Inventory-II (BDI-II), the Matson Social Skills Questionnaire, and the Self-Regulation Questionnaire by Brown et al. (1999). Statistical analyses were conducted using multivariate analysis of covariance (MANCOVA).Findings: Inferential statistics indicated that kindness behavior training had a significant effect on all three dependent variables. Post-test results showed a significant reduction in depression scores (F = 16.221, p < .001, η² = .278), a significant improvement in interpersonal communication skills (F = 18.499, p < .001, η² = .416), and a significant increase in self-regulation skills (F = 43.542, p < .001, η² = .626) in the experimental group compared to the control group. The results confirm that KBT contributed meaningfully to the psychological recovery of the participants.Conclusion: Given the positive outcomes, KBT may serve as a valuable adjunct to standard substance use treatments, particularly when addressing emotional dysregulation and interpersonal dysfunction in comorbid depression.